2013
DOI: 10.4161/hv.23601
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine administration and the development of immune thrombocytopenic purpura in children

Abstract: The most important reasons cited by the opponents of vaccines are concerns about vaccine safety. Unlike issues such as autism for which no indisputable documentation of direct relationship with vaccine use is available, immune thrombocytopenic purpura (ITP) is an adverse event that can really follow vaccine administration, and may limit vaccine use because little is known about which vaccines it may follow, its real incidence and severity, the risk of chronic disease, or the possibility of recurrences after ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 44 publications
3
78
0
4
Order By: Relevance
“…Another confirmed autoimmune adverse effect associated with vaccination is the induction of idiopathic thrombocytopenia (ITP), also known as immune thrombocytopenia, following the measles-mumps rubella (MMR) vaccine, in particular within 6 weeks of immunization [95][96][97]. ITP is an autoimmune condition, clinically characterized by low platelet count (less than 100,000 platelets per microliter) due to increased destruction and impaired platelet production, and by the presence of autoantibodies (IgG) directed toward platelet membrane antigens (glycoproteins IIb-IIIa) [98].…”
Section: Mmr Vaccine and Idiopathic Trombocytopeniamentioning
confidence: 99%
“…Another confirmed autoimmune adverse effect associated with vaccination is the induction of idiopathic thrombocytopenia (ITP), also known as immune thrombocytopenia, following the measles-mumps rubella (MMR) vaccine, in particular within 6 weeks of immunization [95][96][97]. ITP is an autoimmune condition, clinically characterized by low platelet count (less than 100,000 platelets per microliter) due to increased destruction and impaired platelet production, and by the presence of autoantibodies (IgG) directed toward platelet membrane antigens (glycoproteins IIb-IIIa) [98].…”
Section: Mmr Vaccine and Idiopathic Trombocytopeniamentioning
confidence: 99%
“…kod visoko predisponirane jedinke pod odgovarajućim okolnostima). Uistinu, objavljeni primeri povezanosti autoimunskih oboljenja i pojedinih vakcina uključuju Guillian-Barre -ov sindrom [7] i imunsku trombocitopenijsku purpuru [8]. Takve povezanosti se, međutim, beleže veoma retko, a uzročno-posledičnu vezu je, usled ekstremno male učestalosti događaja, teško potvrditi standardnim statističkim metodama [9].…”
Section: Vakcine I Imunitet: "Velika Tri" Argumentaunclassified
“…ITP is an adverse event that rarely follows vaccine administration and thus should not limit vaccine use. Cecinati et al 6 found that ITP is very rare and that the only vaccine for which there may be a demonstrated cause-effect relationship is the measles, mumps, and rubella (MMR) vaccine that can occur in only 1-3 children in every 100,000 vaccine doses.…”
Section: Discussionmentioning
confidence: 99%